SEASONAL FLUCTUATIONS IN TOMATO PRICES AND THEIR CORRELATION WITH EXPORT PRICES: THE CASE OF TÜRKİYE - Merve Mürüvvet DAĞ; Mevlüt GÜL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Tomatoes are emphasized as an important agricultural product both globally and in Türkiye; this product has a large domestic market and export volume. This study examines the seasonal fluctuations and price trends of tomatoes using data from the Istanbul Metropolitan Municipality Wholesale Fruit and Vegetable Market Directorate. The results revealed that tomato prices in Türkiye exhibit significant seasonal changes throughout the year, with prices generally being high in the first months and low during the summer months. Additionally, despite a decrease in Türkiye’s tomato export volume from 2018 to 2022, export values increased, and unit prices rose. The correlation analysis of export prices identified relationships between Türkiye and other tomato-producing countries, showing that these relationships have significant impacts on price dynamics and trade strategies. The study emphasizes the importance of continuous monitoring and strategic planning to adapt to changes in agricultural conditions and market demands.